An Investigation on the possibility of utilizing domestic wood in cooling towers - Fardad Golbabaei (Regional Information Center for Science and Technology (RICeST), 2010)
Most industrial production processes need cooling water to operate efficiently and safely. Refineries، steel mills، petrochemical manufacturing plants، electric utilities and paper mills all rely heavily on equipment or processes that require efficient temperature control. Cooling water system control these temperatures by transferring heat from hot process fluids into cooling water. As this happens، the cooling water itself gets hot before it can be used again it must either be cooled or replaced by a fresh supply of cold water. The aim of this study was utilizing domestic wood in cooling towers structure. For this purpose، five wood spices included: Hornbeam، Oak، Alder،Populus and Tehran pine (Eldarica pine) and also five different regions with different climate، included: electric plant Montazer ghaem from Karaj near of Tehran، electric plant Loshan from north of Iran، electric plant Dorcheh Esfahan from center of Iran and petrochemical manufacturing plants Bandar emam from south of Iran، have been chosen. Sampling have been done and treated with CCA. All samples were put in the cooling towers and were tested during the study period. (Mechanical tests such as specific gravity، static bending، compression parallel to grain and hardness).  Based on this study، the mechanical properties of these spices during last four years were done. At the fifth year of study، virtual damages have not seen where as significant difference have been achieved in aspect of mechanical properties. Among of theses wood spices، Populous and Pinus eldarica had minimum mechanical degrade and it should be noted that Pinus eldarica spices had better quality than populous spices.